Blood biochemical profile in normal cyclical and anoestrus cows - Arosh, A Joe; Kathiresan, D; Devanathan, T G; Rajasunadaram, R C; Rajasekaran, J (The Indian Journal of Animal Sciences, 2012)
Blood serum biochemical constituents were analyzed in 6 normal cyclical cows and 6 anoestrus Jersey crossbred cows. Total protein, albumin, globulins, cholesterol, glucose, calcium, inorganic phosphorus, sodium, chloride, potassium, alkaline phosphatases and SGOT were significantly (P < 0.01) lower in anoestrus cows than that of normal cyclical cows. The possible role of these blood serum constituents in reproduction is discussed.